2003
DOI: 10.1046/j.1365-2672.2003.01960.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of killing of Bacillus subtilis spores by hypochlorite and chlorine dioxide

Abstract: Aims: To determine the mechanisms of Bacillus subtilis spore killing by hypochlorite and chlorine dioxide, and its resistance against them. Methods and Results: Spores of B. subtilis treated with hypochlorite or chlorine dioxide did not accumulate damage to their DNA, as spores with or without the two major DNA protective α/β‐type small, acid soluble spore proteins exhibited similar sensitivity to these chemicals; these agents also did not cause spore mutagenesis and their efficacy in spore killing was not inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
264
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(284 citation statements)
references
References 51 publications
18
264
0
2
Order By: Relevance
“…Rapid inactivation of Bacillus spores with oxidizing biocides is largely dependent on the agent's ability to degrade the spore coats (4,13). Once the coats are penetrated, the inner membrane and cell wall can be damaged, causing hydration of the cell core, leading to death (29). The hydrophobic nature of the exosporium may also contribute to biocide resistance (28).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid inactivation of Bacillus spores with oxidizing biocides is largely dependent on the agent's ability to degrade the spore coats (4,13). Once the coats are penetrated, the inner membrane and cell wall can be damaged, causing hydration of the cell core, leading to death (29). The hydrophobic nature of the exosporium may also contribute to biocide resistance (28).…”
Section: Discussionmentioning
confidence: 99%
“…This cotE spore coat defect is also indicated by their increased sensitivity to lysozyme and hypochlorite, as compared with that of wild-type spores (Table 1) (5,7,17,19). To obtain further insight into the role of the spore coat in resistance to predation, spores of strains with mutations affecting the spore coat to different degrees were examined.…”
Section: Ingestion and Digestion Of Spores Of B Subtilis Strains Witmentioning
confidence: 99%
“…The coat does protect against some, although not all chemicals, perhaps by serving as a reactive armor that detoxifies harmful chemicals before they damage essential components located further within the spore (1,7,19). However, it seems unlikely that the complex spore coat would have evolved solely to allow the dormant spore to resist toxic chemicals.…”
mentioning
confidence: 99%
“…Following the 9-11 attacks in the USA, ClO 2 gas was used to treat the Bacillus anthracis spores detected in certain government buildings and on the exterior of mail packages addressed to a small number of government institutions (EPA, 2006;Canter et al, 2005). Finally, various studies have demonstrated the efficiency of ClO 2 in deactivating Bacillus endospores (surrogates for B. anthracis spores) (Buttner et al, 2001;Cortezzo et al, 2004;Young and Setlow, 2003).…”
Section: Introductionmentioning
confidence: 99%